2022
DOI: 10.3389/fendo.2022.1015516
|View full text |Cite
|
Sign up to set email alerts
|

Association between rheumatoid arthritis and thyroid dysfunction: A meta-analysis and systematic review

Abstract: ObjectiveRheumatoid arthritis (RA) is an autoimmune disorder. Multiple studies have investigated the risk of thyroid dysfunction in patients with RA but have reached conflicting conclusions. This systematic review aimed to determine whether patients with RA are at higher risk of thyroid dysfunction.MethodsWe comprehensively reviewed online literature databases, including PubMed, Scopus, Embase, and the Cochrane Library, from their respective inception dates to March 25, 2022. Studies that provided data on at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…reported that the different presence of hypothyroid disease between cohorts of patients with or without RA was not significant at the time of RA diagnosis in the earlier stage ( 12 ). Recently, the meta-analysis also showed that the risk of developing thyroid dysfunction particularly hypothyroidism was increased in RA patients ( 13 ). However, in many cases, the earlier diagnosed RA or hypothyroidism does not mean that it begins earlier; the relationship between hypothyroidism and RA remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the different presence of hypothyroid disease between cohorts of patients with or without RA was not significant at the time of RA diagnosis in the earlier stage ( 12 ). Recently, the meta-analysis also showed that the risk of developing thyroid dysfunction particularly hypothyroidism was increased in RA patients ( 13 ). However, in many cases, the earlier diagnosed RA or hypothyroidism does not mean that it begins earlier; the relationship between hypothyroidism and RA remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also discovered that (subclinical) hyperthyroidism and (subclinical) hypothyroidism are both found to be closely related to rheumatoid arthritis. [29] Autoimmune diseases often lead to endothelial cell damage and increase the incidence of VTE. Therefore, this may also factor in the increased risk of VTE in patients with thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune polyendocrine syndrome 3 involving autoimmune thyroid disease can also be comorbid with RA and myasthenia gravis. Liu et al [7] conducted a metaanalysis of the 29 research papers available to May 2022. They examined 35,708 cases of patients in terms of possible coexistence of RA and thyroid disorders, confirming the high incidence of AID, especially hypothyroidism, in this group of patients.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%